Mauzoleum przekształcone w elitarny cmentarz? o początkach nekropoli w Bodzi - Buko, Andrzej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
The elite cemetery in Bodzia (from the late 10th to the early 11th centuries) hosts the deceased of foreign and local origin who had a strong sense of ideological and ethno-cultural bonds. According to the results of the author’s latest research, a large tomb D162 played a pivotal role in the cemetery. It was originally built as a grave – a mausoleum with an entrance from the east. Over time, more graves with enclosures were added to the existing tomb on the eastern side, imitating architecture of a primary grave. The successive burials in which remains of foreigners were identified represented the structural first degree elements of the cemetery. In line with the results of isotopic labelling, the group of people buried in this row is associated with newcomers from the Baltic (Scandinavian) zone. In search of the sources of the idea and, further on, the model of the cemetery, attention was directed at the symbols and the structural elements of royal courts and rural aristocratic mansions, especially rectangular plots of land with enclosures as known from Denmark. In the light of newer research, the most symbolic representations include the topography and structural elements identified around the royal kurgans in Jelling.